INTERNAL AUDIT AS A STRATEGIC RISK MANAGEMENT TOOL: A BIBLIOMETRIC ANALYSIS OF PUBLIC SECTOR EVOLUTION - Zulkiffly Baharom (Journal of Business Management and Accounting)
This study investigates the evolution and current landscape of internal audit as a strategic risk management mechanism in the public sector through a comprehensive bibliometric analysis. By examining publication patterns, influential contributions, and emerging research trends, the study addresses significant knowledge gaps in understanding how internal audit functions have evolved from traditional compliance roles to strategic risk management tools. The analysis encompasses 1,132 publications from the Scopus database (1978-2024), employing ScientoPy for bibliometric evaluation and VOSviewer for network visualization. Results demonstrate robust research expansion, with an annual growth rate of 27%, reflecting increasing scholarly recognition of the internal audit's strategic importance. The field has developed substantial scholarly impact (h-index: 66), with leading contributions from the United States and China and prominent publication venues including the Managerial Auditing Journal and Accounting Horizons. Keyword network analysis reveals three distinct research clusters centered on internal audit methodologies, risk management frameworks, and strategic public sector governance. The research identifies emerging trends such as digital transformation, sustainability assurance, and integrated risk governance. This research contributes to both theory and practice by mapping the intellectual landscape of internal audit's strategic evolution, identifying critical research gaps, and providing a foundation for future scholarly inquiry. The findings offer valuable insights for internal audit practitioners, public sector managers, and policymakers navigating contemporary governance challenges.